CHRISTIAN RELIGION IN THE GLOBALISED WORLD OF THE XXI stCENTURY - Pukenis, Robertas (European Scientific Journal, ESJ, 2014)
This article helps to perceive the influence of the world globalisation to religion by proving that Church itself also has the features of globalisation. The end of the XX th century was dramatically marked by the movements of two trends. Nations fought for independence by creating national states. The states which “ran” away from the Soviet block made their own sovereign republics and there appeared 15 separate subjects of international law out of 15 states which made the Soviet Union. In order to keep independence the new states unite by new economical, political and military ties. European Union is nothing else than a form of new globalisation uniting already 28 European states and having over 500 million of inhabitants. It is obvious that national movements destroy globalisation and unite among each other by different forms. For the sake of freedom they have to be globalised. Catholic Church and other Christian communities brought a great contribution into the establishment of EU in uniting the nations by Christian culture. Concentrating on the object of „globalisation“we shall analyse the hypothesis how religion survives in the context of globalisation. Doe religion influence globalisation? Historical and analytical method will be used.